Ethics of description - Reeck, Matt, author.
1 online resource (xiv, 264 pages)
Keywords: "Ethics of Description: The Anthropological Dispositif and French Modern Travel Writing follows the development of a minor tradition in French literature where metropolitan authors traveling abroad demonstrate their awareness of the ethical conundrums of representing world peoples. During the colonial-modern era, currents of anthropological thought and representational practice are identifiable throughout society, and across literature, the arts, and the sciences. Collectively, they can be theorized as belonging to a dispositif, the anthropological dispositif. The modernization of anthropology serves as an ambivalent interlocutor for the realizations of the writers studied in this book about the difficulties of describing cultural realities that lie largely outside their ken. Anthropology motivates new literary representational strategies that are, alternatively, in keeping with scientific mandates or operate against them. Forty images are analyzed alongside literary works. A postcolonial chapter shows how the ethical awareness of the colonial-modern authors studied have impacted minority self-representation in contemporary France"--